Discharge Flow of Spherical Particles from a Cylindrical Bin: Experiment and DEM Simulations - Rafał Kobyłka (MDPI AG, 2021)
A series of the DEM simulations of the outflow of wooden spheres from a flat-bottomed container was reported, considering the maximum diameter to arrest the flow. Numerical simulations of the discharge process were performed, and the micro-mechanics of the discharged particles were described. The effect of the sliding friction coefficient between particles, rolling friction coefficient, and modulus of elasticity of particles on the clogging process was investigated. The results of the simulations of the mass flow rate of spheres have shown a fairly close agreement with the experimental results. The real particles of wood were not perfectly spherical, their properties were anisotropic, and their frictional properties were non-homogenously distributed on the surface. Nevertheless, these deviations from ideal conditions did not produce a considerable discrepancy in the results. No direct relationship between the interparticle friction and the clogging was found; however, a relationship between the stability of the dome formed at flow arrest and the rolling friction was observed. An increase in Young’s modulus of particles by two orders of magnitude did not affect the clogging process, but a slightly higher probability of clogging was found for softer particles.